Dosimetry of permanent interstitial prostate brachytherapy for an intraoperative procedure, using O-arm based CT and TRUS - Ishiyama, Hiromichi; Sekiguchi, Akane; Satoh, Takefumi; Tsumura, Hideyasu; Takenaka, Kouji; Kawakami, Shogo; Tabata, Ken-ichi; Kobayashi, Kentaro; Iwamura, Masatsugu; Hayakawa, Kazushige (Journal of Contemporary Brachytherapy, 2016)
Purpose: The aim of this report is dosimetric evaluation for an intraoperative fusion computed tomography (CT) as a superior predictor of 1-month CT based dosimetry in comparison to transrectal ultrasound (TRUS) in permanent interstitial prostate brachytherapy. Material and methods : Data of 65 patients treated with seed implantation were analyzed. All procedures has been performed with patients in the lithotomy position inside the O-arm system. An end-fine probe is used as a landmark to fuse TRUS and O-arm-based CT images. There was no difference in the patient’s position, probe position, and timing of image acquisition between the two imaging modalities. Dose-volume histogram (DVH) parameters such as the dose to 90% of prostate volume (D 90 ) has been analyzed. Results: The area under the curve of the receiver operating characteristic tended to be larger on fusion CT than on TRUS for most DVH parameters (71.85% vs. 59.59% for D 90 ; p = 0.07). Significant relationships between fusion CT and 1-month CT were confirmed using Pearson’s correlation coefficients for most DVH parameters (R = 0.48, p < 0.01 for D 90 ), although the relationship between TRUS and 1-month CT was poor. Large dose reduction (35 Gy for D 90 ) was seen from TRUS to fusion CT, especially in patients with high body weight and small prostate volume. Conclusions : Intraoperative fusion CT appears to have higher predictive power for 1-month CT-based dosimetry than TRUS. A prospective trial using fusion CT-based planning is warranted.